Unveiling Misconceptions: A Multilocation Study on First-Year College Students in Indonesia - Muliyani, Riski; Suhandi, Andi; Prima, Eka Cahya; Muslim, Muslim (UIN Sunan Gunung Djati Bandung, 2024)
The aim of this research is to determine whether there are any misconceptions among first-year students regarding the concepts of heat and temperature. This study employs a descriptive research design. The sample used in this study consists of 224 first-year students from both public and private universities in the cities of Singkawang, Bima, Madiun, and the districts of Sumedang, Sintang, and Bandung. Data were collected through a g-form using a four-tier test instrument. The research results indicate that the percentage of misconceptions among students on the concepts of temperature and heat is highest in the sub-topic